2007
DOI: 10.1100/tsw.2007.234
|View full text |Cite
|
Sign up to set email alerts
|

Drugs of Abuse Can Entrain Circadian Rhythms

Abstract: Circadian rhythms prepare organisms for predictable events during the Earth's 24-h day. These rhythms are entrained by a variety of stimuli. Light is the most ubiquitous and best known zeitgeber, but a number of others have been identified, including food, social cues, locomotor activity, and, most recently drugs of abuse. Given the diversity of zeitgebers, it is probably not surprising that genes capable of clock functions are located throughout almost all organs and tissues. Recent evidence suggests that dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 70 publications
0
62
0
Order By: Relevance
“…Physiological, behavioral, and molecular rhythms are all affected by rewarding stimuli, including drugs of abuse and food. Rodent studies have shown that prolonged alcohol treatments can disrupt the circadian pattern of a variety of hormonal and behavioral rhythms (Kakihana and Moore, 1976;Kosobud et al, 2007, Madeira et al, 1997Rajakrishnan et al, 1999;Rosenwasser et al, 2005;Spanagel et al, 2005a). However, the molecular mechanisms of these disruptions are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological, behavioral, and molecular rhythms are all affected by rewarding stimuli, including drugs of abuse and food. Rodent studies have shown that prolonged alcohol treatments can disrupt the circadian pattern of a variety of hormonal and behavioral rhythms (Kakihana and Moore, 1976;Kosobud et al, 2007, Madeira et al, 1997Rajakrishnan et al, 1999;Rosenwasser et al, 2005;Spanagel et al, 2005a). However, the molecular mechanisms of these disruptions are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies exploring circadian rhythms and human drug addiction suggest chronic drug use commonly results in severe circadian alterations, not entrainment (see review in Hasler et al (2012) and Wasielewski & Holloway (2001)). However, other animal studies indicate psychoactive drugs of abuse (cocaine, methamphetamine, fluoxetine, nicotine, alcohol) can assist in entraining SCN-independent pacemakers (Kosobud et al, 2007;Manev & Uz, 2006). These SCN-independent pacemakers have been located in the parietal cortex, nucleus accumbens and caudate putamen, all areas of the brain also affected by cannabinoids (Akhisaroglu et al, 2004;Brievogel & Childers, 1998;Falcón & McClung, 2009;Masubuchi et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, alcohol and psychostimulants, like cocaine, nicotine and amphetamines, have all demonstrated circadian sensitivity (Falcón & McClung, 2009;Iijima et al, 2002;Kosobud et al, 2007;McClung, 2007). Specifically, rodents are inclined to seek and prefer alcohol and stimulants at particular hours and are physiologically more responsive to these substances at specific times throughout the 24-h day (see review in Kosobud et al (2007)). Further, Falcón & McClung (2009) demonstrated stimulants and alcohol have similar interactions with the circadian timing mechanism and individuals dependent on these substances have alterations in their activity cycle, sleep/wake cycle and body temperature.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations